TRADISI RITUAL SUNGKAWIANO SANGIA PADA ETNIS BUTON DI KECAMATAN SIOMPU KABUPATEN BUTON SELATAN - Harfita Harfita; La Ode Dirman; samsul samsul (Laboratorium Jurusan Arkeologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2019)
This study aims to understand the ritual process of Sungkawiano Sangia in Buton ethnic in Siompu Sub district, South Buton Regency and find out the symbolic meaning contained in the Sungkawiano Sangia Ritual for Buton Ethnic in Siompu sub-district, South Buton Regency. This research was conducted in Siompu District, South Buton Regency. The method in this study is descriptive qualitative. Primary data obtained throughin-depth interviews with parties found using purposive sampling technique, as well as direct observation in thefield. Secondary data obtained from data collection through documents related to the topic of research. The datacollected was analyzed using the theory of symbolic interaction (Herbert Blummer).The results of this study are:The process of carrying out the sungkawiano sangia ritual consists of three stages, namely the stage ofdeliberation, preparation, and procession. The symbolic meaning in this sungkawiano sangia ritual is: white riceas a symbol of chastity, yellow janur as a symbol of beauty, eggs as a symbol of determination, kalumpi askapanaando sumanga, incense as a symbol of bringing spirits, young coconut water as a symbol of calm seawater.